2010
DOI: 10.1100/tsw.2010.99
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Circuits of Resolution in the Eye

Abstract: Lipid autacoids have well-established key roles in physiology and pathophysiology. Eicosanoids derived from ω-6 arachidonic acid (AA) have long been recognized for their roles in cardiovascular and renal functions, and vascular tone, as well as regulating inflammatory and immune functions. It is now appreciated that AA is a substrate for generating lipid mediators with anti-inflammatory and proresolving properties, namely lipoxins (i.e., LXA4), which are an integral component for the successful execution of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 184 publications
(287 reference statements)
0
15
0
Order By: Relevance
“…UVB light was also found to increase cornea epithelial mRNA expression for the platelet and epithelial forms of 12-LOX, as well as 15-LOX-2, enzymes mediating the generation of anti-inflammatory and protective lipid mediators, including the lipoxins and the docosahexaenoic acid-derived protectins and resolvins [50, 51]. Recent studies have shown that lipid mediators such as lipoxin A 4 and the neuroprotectin D1 are generated in the cornea where they inhibit chemokine formation and promote corneal wound healing [52, 53].…”
Section: Discussionmentioning
confidence: 99%
“…UVB light was also found to increase cornea epithelial mRNA expression for the platelet and epithelial forms of 12-LOX, as well as 15-LOX-2, enzymes mediating the generation of anti-inflammatory and protective lipid mediators, including the lipoxins and the docosahexaenoic acid-derived protectins and resolvins [50, 51]. Recent studies have shown that lipid mediators such as lipoxin A 4 and the neuroprotectin D1 are generated in the cornea where they inhibit chemokine formation and promote corneal wound healing [52, 53].…”
Section: Discussionmentioning
confidence: 99%
“…15-LOX-LXA 4 -ALX/FPR2 circuit has been identified as an important resident circuit that controls wound healing and immune responses at the ocular surface. Two 15-LOX enzymes ( ALOX15, ALOX15B ) have been identified in the human cornea [14, 15, 16] and the mouse homolog 12/15-LOX ( Alox15 ) is expressed in the corneal epithelium, retinal pigment epithelium (RPE) and lens [17, 18]. Knockdown of 15-LOX ( ALOX15 ) in the human RPE increased susceptibility to oxidative stress induced apoptosis [19].…”
Section: Introductionmentioning
confidence: 99%
“…This pathway is significantly amplified by the recruitment of specific polymorphonuclear (PMN) leukocytes and macrophage populations that carry 5‐LOX and/or 15‐LOX, which sets in motion a temporally defined counterregulatory program that drives inflammatory resolution. A striking feature in both mouse and human corneas is the high epithelial expression of 15‐LOX (21, 33) and the expression of the ALX receptors (29, 31, 33, 34). Acute and chronic inflammation selectively regulates expression of 15‐LOX and ALX receptors.…”
mentioning
confidence: 99%